Reliability models for engineers and scientists - Kaminskiy, Mark (CRC, 2013)
A discussion of the basic reliability concepts and models, this book is suitable for students of reliability engineering as well as for those who wish a supplement on applied survival data analysis. The models discussed in the book are used in reliability, risk analysis, physics of failure, fracture mechanics, biological, pharmaceutical and medical studies. It is an up- to-date, concise, and informative handbook on reliability models, which does not require any special mathematical background. It also introduces a new concept of the Gini-type index